From the forest to the coast: the wild meat trade chain on the Coast of Guyana - Vliet, N. van; Puran, A.; David, O.; Nasi, R. (Universidade Estadual da Paraiba/Universidade Federal Rural de Pernambuco (Ethnobiology and Conservation), 2022)
In the Caribbean region, very little is known about wild meat use and trade. To contribute to this knowledge gap, we studied the wild meat trade chain on the coastal area of Guyana, which geographically and culturally connects the Caribbean and the Amazon Region. In Guyana, the wildmeat sector is legal and in the process of being regulated. Our study shows that the market chain on the coast of Guyana is a short and direct market chain where the harvester most often sells directly to the consumer or through one level of intermediary (market vendors, home-based traders, roadside traders, restaurants, food stalls or rum shops). In coastal Guyana, wild meat can be considered a luxury, rather than a necessity: the price is higher compared to other alternative sources of meat and demand rises for special events. The topmost sold species are Cuniculus paca, Mazama americana, Tapirus terrestris, Dicotyles tajacu, Tayassu pecari, and Hydrochoerus hydrochaeris. The volumes traded to the coast of Guyana are equivalent to 361 tons of wild meat sold per year. Considering the population size on the coast of Guyana, this amount is equivalent to 1,4 g/capita/day and 4% of the protein intake from animal origin. These values are below those observed in urban towns from Central Amazonia in Brazil where wild meat consumption per capita equals to 18 g/capita/day. From a one health perspective, further attention is required with regards to food safety aspects along this legal trade chain.